Traumatismo raquimedular: aspectos epidemiológicos, clínicos e radiológicos - Morais, Dionei Freitas (2013)
Introduction: The spinal cord injury (SCI) it is any aggression that entails anatomic lesion or functional neural elements, within the spinal canal with or without fractures and / or vertebral displacement, resulting in temporary or permanent change in motor, sensory or autonomic. Objective: article 1: To investigate the epidemiological profile of victims of SCI treated at tertiary hospital. Article 2: To evaluate the clinical application of MRI in victims of SCI, considering the type, extent and severity of injury, and clinical and radiological correlation. Article 3: To evaluate complications and injuries associated with neurological severity, vertebral segment, length of stay and mortality in patients with SCI. Methods: Article 1: A descriptive, cross-sectional, prospective study, 321 patients with SCI of the Hospital de Base de São José do Rio Preto, performed January/2008 to June/2012. Analyzed the following variables: gender, age, marital status, occupation, education, religion, origin, etiology, morphology and region of the lesion; neurological status and associated injuries. Article 2: Analyzed the tests diagnostic imaging (CT and MRI), to verify the clinical value in the diagnosis of patients with SCI, by radiological findings of CT and MRI. Article 3: Analyzed the data related to the patient (age, sex), cause of the accident, anatomic distribution of injury, neurological status, associated injuries and in-hospital complications / mortality. Results: Article 1: Was found in the sample: 72% male, 28% female; prevalent age group: 21-30 years; marital most frequent: stable (46.8%), level of education: incomplete primary education (57%); most common cause: accidents automotive (38.9%); over this injury: burst fracture (23.7%); most affected region: cervical subaxial (C3-C7) (41.7%); injury associated more present: head injury trauma (TBI) (28.2%), neurological status on admission found more / High: ASIA-E. There were 25 deaths (7.8%), with 76% lesion in the cervical region were stratified with ASIA-A, and 68% had respiratory complications. Article 2: Radiological findings were best visualized on MRI, except the posterior elements (p = 0.001) were more frequently diagnosed on CT. 271 lesions were diagnosed, 271 of these by MRI, CT and 154 for 100 (36.9%) detected simultaneously, thus, MRI detected more than 117 injuries in CT. Article 3: 231 patients (72%) were male and 90 (28%) were female with a mean age of 42.68 years. 170 patients had lesions associated with SCI. The most common injury was TBI in 48 (28.2%), and 25 (8%) patients died. Conclusion: Article 1: The SCI affected more young adult males with stable relationship and low level of education. The most common cause was automobile accident, type of injury was burst fracture, and cervical region the most affected. The severity of the neurological status was related to cervical involvement and increased the risk of respiratory complications and mortality. Article 2: The MRI detected more lesions compared with CT, and is useful in diagnosing soft tissue injuries and intrathecal. Article 3: The SCI was more frequent and associated with the presence of higher TBI quantity of lesions increases the risk of death.